2020
DOI: 10.21203/rs.3.rs-54657/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noise2Atom: Unsupervised Denoising for Scanning Transmission Electron Microscopy Images

Abstract: We propose an effective deep learning model to denoise scanning transmission electron microscopy (STEM) image series, named Noise2Atom, to map images from a source domain S to a target domain C, where S is for our noisy experimental dataset, and C is for the desired clear atomic images. Noise2Atom uses two external networks to apply additional constraints from the domain knowledge. This model requires no signal prior, no noise model estimation, and no paired training images. The only assumption is that the inp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Convolutional neural networks (CNNs) achieve state-of-theart denoising performance on natural images (Zhang et al, 2017;Tian et al, 2019) and are an emerging tool in various fields of scientific imaging, for example, in fluorescence light microscopy (Belthangady & Royer, 2019;Zhang et al, 2019) and in medical diagnostics (Yang et al, 2017;Jifara et al, 2019). In electron microscopy, deep CNNs are rapidly being developed for denoising in a variety of applications, including structural biology (Buchholz et al, 2019;Bepler et al, 2020), semiconductor metrology (Chaudhary et al, 2019;Giannatou et al, 2019), and drift correction (Vasudevan & Jesse, 2019), among others (Ede & Beanland, 2019;Lee et al, 2020;Wang et al, 2020;Lin et al, 2021;Spurgeon et al, 2021), as highlighted in a recent review (Ede, 2020). CNNs trained for segmentation have also been used to locate the position of atomic columns (Lin et al, 2021) as well as to estimate their occupancy (Madsen et al, 2018) in relatively high SNR (S)TEM images (i.e., SNR = ∼10).…”
Section: Introductionmentioning
confidence: 99%
“…Convolutional neural networks (CNNs) achieve state-of-theart denoising performance on natural images (Zhang et al, 2017;Tian et al, 2019) and are an emerging tool in various fields of scientific imaging, for example, in fluorescence light microscopy (Belthangady & Royer, 2019;Zhang et al, 2019) and in medical diagnostics (Yang et al, 2017;Jifara et al, 2019). In electron microscopy, deep CNNs are rapidly being developed for denoising in a variety of applications, including structural biology (Buchholz et al, 2019;Bepler et al, 2020), semiconductor metrology (Chaudhary et al, 2019;Giannatou et al, 2019), and drift correction (Vasudevan & Jesse, 2019), among others (Ede & Beanland, 2019;Lee et al, 2020;Wang et al, 2020;Lin et al, 2021;Spurgeon et al, 2021), as highlighted in a recent review (Ede, 2020). CNNs trained for segmentation have also been used to locate the position of atomic columns (Lin et al, 2021) as well as to estimate their occupancy (Madsen et al, 2018) in relatively high SNR (S)TEM images (i.e., SNR = ∼10).…”
Section: Introductionmentioning
confidence: 99%
“…These methods are called full-reference, emphasizing the need for high-quality reference data [28, 45]. SSIM and consecutive similarity (CSS) metric, which is a variation of SSIM [46], are in this category. We used (local) SSIM, which provides an error map by structurally comparing the reconstructed image with the reference image, and based on that error map controlled for reconstruction defects.…”
Section: Discussionmentioning
confidence: 99%
“…The first, second and the third term are respectively called luminance (mean), contrast (standard deviation) and structural (covariance). As the standard deviation of an image is not usually affected by denoising [46], in our experiment, we only focused on luminance and structural term and we investigated how luminance and structural terms of SSIM depend on the duration of photon collection in integrating versus averaging mode detectors. We observed that, for integrating detectors, the mean term influences the SSIM value, so that structural reliability cannot be directly compared if this term is included in the calculation of the SSIM value (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the TEM data in our case study, unsupervised denoising does not perform well (see Section 6, and in particular Figures 16, and 17), possibly due to the SNR, which is orders of magnitude lower (around 3 dB) than that reported in these works (around 27 dB for Zhang et al (2019)). Improving the performance of unsupervised denoising methods at low SNRs is thus an important topic for future research - Wang et al (2020) have reported promising results in this direction for scanning TEM.…”
Section: Related Workmentioning
confidence: 99%